INTEGRATED MANAGEMENT OF ALTERNARIA BLIGHT IN INDIAN MUSTARD1 - DINESH RAI; A. K. MISHRA; ANIL PANDEY (The Bioscan, 2014)
Field trials were carried out during Rabi 2008-09 and 2009-10 crop seasons to test the efficacy of different fungicides and bioagents, as seed treatment and foliar spray against Alternaria blight disease. Among the eight treatments, seed treatment combination of Metalaxyl with Carbendazim was most effective in reducing disease severity and increasing yield (35.0 and 24.0 %) followed by Carbendazim (31.5 and 23.3%) and Metalaxyl (29.3 and 20.3%) alone respectively. In case of seed treatment and foliar spray of Metalaxyl with Mancozeb was found most effective in reducing disease severity and increasing yield (44.0 and 37.6%) followed by Carbendazim with Ridomil MZ (41.2 and 33.5%), Trichoderma harzianum with Pseudomonas fluorescence (28.0 and 12.0%) and T. harzianum with T. harzianum (26.9 and 14.0%) compare to control.